2005
DOI: 10.1111/j.1368-5031.2005.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Focus on trial endpoints of clinical relevance and the use of almotriptan for the acute treatment of migraine

Abstract: Almotriptan is a 5-HT(1B/1D) receptor agonist, or triptan, indicated for the acute treatment of migraine. It has been shown to be effective and well tolerated for the treatment of acute migraine in approximately 5000 patients enrolled in short-term placebo- and active-controlled trials and long-term open-label trials. A recent meta-analysis reported that almotriptan has the highest sustained pain-free (SPF) rate and lowest adverse-event (AE) rate of all oral triptans. Sustained pain free is a composite endpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…A meta‐analysis of 53 clinical trials of six oral triptans reported that almotriptan had the highest SPF rate of all the triptans [16]. When SNAE was calculated from the meta‐analysis data, this high SPF rate along with a low AE rate translated to almotriptan also having the highest SNAE rate [17]. The results of this current trial are consistent with the high SPF and SNAE rates for almotriptan reported earlier, almost twice that achieved here by ergotamine plus caffeine.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis of 53 clinical trials of six oral triptans reported that almotriptan had the highest SPF rate of all the triptans [16]. When SNAE was calculated from the meta‐analysis data, this high SPF rate along with a low AE rate translated to almotriptan also having the highest SNAE rate [17]. The results of this current trial are consistent with the high SPF and SNAE rates for almotriptan reported earlier, almost twice that achieved here by ergotamine plus caffeine.…”
Section: Discussionmentioning
confidence: 99%
“…The design for the simulations thus uses 3 5 = 243 conditions for the true distributions. Each condition was run with 1000 replications, thereby yielding 243 × 1000 = 243,000 simulation outcomes in total (based on 243,000 × 2 × 300 = 145,800,000 patients).…”
Section: Description Of the Simulationsmentioning
confidence: 99%
“…We refer to and treat these five estimates as the “true” values. We calculated z W for all 2 5 = 32 possible combinations of hypothesized and true parameter values, to enable us to assess how results could be affected by the misjudgment inherent in the hypothesized-versus-true discrepancy. Besides these 32 z W -values, we found the (single) values of z LRNF and z LRF .…”
Section: Examplementioning
confidence: 99%
See 1 more Smart Citation
“…More recently, in order to represent more accurately what migraine patients want from their acute migraine therapy, composite endpoints encompassing the measures able to predict patient satisfaction (such as pain-free state, use of rescue medication, AEs) have been developed and introduced (Sandrini et al 2005). …”
Section: Introductionmentioning
confidence: 99%